Synaptic Pruning in Alzheimer#x2019;s Disease: Role of the Complement System (Global Journal of Medical Research, 2020)
Alzheimer#x2019;s disease (AD) continues to threaten aged individuals and health care systems around the world. Human beings have been trying to postpone, reduce, or eliminate the primary risk factor for AD, aging, throughout history. Despite this, there is currently only symptomatic treatment for AD and this treatment is limited to only a handful of FDA approved AD drugs.